SYNCHRONOUS BRAIN AND LUNG TUBERCULOMA: A CASE SERIES - Ibrahim, Sabri; L, Lina (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Brain tuberculoma is a rare manifestation of tuberculosis that is considered one of the most severe cases of tuberculosis. In this case series, clinical features, radiological findings, and management of the tuberculomas are discussed. Case report: We report three cases of synchronous brain and lung tuberculomas that present different symptoms but demonstrate the same pattern of ring enhancement in brain radiological findings and nodule with consolidation on chest X-ray imaging. Two out of three cases underwent craniotomy tumor removal surgery, and the other one had a ventriculoperitoneal shunt placement as an emergency life-saving procedure due to elevated intracranial pressure caused by mass effect of the tuberculoma and started anti-tuberculosis medication subsequently. Conclusion: Brain tuberculomas should always be considered in the differential diagnosis of single or multiple space-occupying brain lesions in tuberculosis-endemic areas or in individuals with a history of prior tuberculosis exposure or infection. Prompt diagnostic investigations, along with pharmacological and possible adjuvant surgical treatment, are required in brain tuberculomas management.